Using contextual information in learners’ spoken language communication: an eye-tracking study - Duck, Geun Yoo; Lee, Junkyu (Penerbit UKM, 2013)
The efficiency of oral communication can vary depending on how quickly language users process not only language but also non-language information and on how that information is used. Various psycholinguistic experiments have shown that first language (L1) users incrementally form a representation by utilizing context information, and furthermore, can predict the forthcoming information. Since this topic has not been sufficiently studied using second language (L2) learners, theory and application of L2 processing are thus insufficient. This study aims to investigate, using an eye-tracking experiment, whether EFL learners can utilize visually presented contextual information during spoken language comprehension. Specifically, it eye tracked the comprehension processes of EFL learners when auditory inputs with four two-dimensional figures (e.g. Where is the large red circle?)were presented. Twenty-four learners with advanced English proficiency were asked to eye-spot figures corresponding to auditory inputs. Two conditions were manipulated in terms of figure size, color, and shape: (1) one pair of contrasting objects and; (2) two pairs of contrasting objects. It was revealed that the eye often moved to the target object before the noun (e.g. circle) was heard, adjectival information (e.g. large, red) being sufficient to restrict the domain of reference to one object in the visual display. Eye movements were thus quicker in the first condition that requires relatively little context information to distinguish the target than in the second condition that does not. The findings suggest that the subjects utilized real-time contextual information and top-down processing strategy of linguistic information in terms of Paul Grice‘s maxim of quantity.